IMPACT OF INTERNET USAGE ON NIGERIA SECONDARY SCHOOL STUDENTS PERFORMANCE: VAR APPROACH - Ihugba, Okezie; Austin, Emenogu; Okonkwo, O.N ,; Duru, E., (IJRDO- Journal of Educational Research, 2021)
Using quarterly data from 1996 to 2019, this study examined the relationship between internet usage and secondary school student performance in Nigeria. Using a systems simultaneous equation, cointegration analysis was established to capture long- and short-run relationships between variables. The simultaneous equation was simulated using the vector auto-regression (VAR) model technique. To explore short-run causality among variables, the researchers used the VAR Granger causality methodology to look at causality correlations between series. The findings show that internet use, the environment, infrastructure, and government policy have no bearing on tertiary school enrollment. The study recommends that the government hire more qualified counsellors to provide correct guidance on how to use the internet properly, as well as increase the education budget to reach the UNESCO recommendation of 25% to enable schools to improve their environment, upgrade infrastructure, and give free internet within the school environment.